First record of trilobites (Arthropoda) from Carboniferous deposits of the Dnipro-Donets Depression, north-eastern Ukraine - Dernov, Vitaly (Geologos, 2024)
A small trilobite faunule consisting of Weberides mucronatus (M’Coy, 1844) and Waribole sp. is described from Serpukhovian (Upper Mississippian) strata of the Sribne-Krasnograd Zone in the Dnipro-Donets Depression (north-eastern Ukraine). Weberides mucronatus has previously been recorded from Serpukhovian levels in the Donets Basin and in the Lviv Palaeozoic Trough in Ukraine, whereas species of Waribole are here recorded from Carboniferous deposits of Ukraine for the first time. This genus is typical of faunal assemblages of the Mississippian-aged Kulm facies, formed under relatively deep-water marine conditions and widely distributed across western and central Europe.